PEMBERDAYAAN TKW PURNA MELALUI PROGRAM KEWIRAUSAHAAN KERAJINAN TANGAN TENUN SONGKET DI DESA TANJUNG DAYANG SELATAN, KECAMATAN INDERALAYA SELATAN - Julius El Roy Marpaung; Dyah Hapsari; Vieronica Varbi Sununianti (Jurnal Media Sosiologi (JMS), 2020)
The thesis entitled “Empowerment of Full Migrant Workers Through of Weaving of Songket Weaving Entrepreneurship Program In Tanjung Dayang Selatan Village, Inderalaya Selatan Subdistrict” examines the empowerment process of full migrant workers through entrepreneurship program in songket weaving craft in Tanjung Dayang Selatan village and strategy to develop songket weaving crafts. This study uses a descriptive research method with a qualitative approach. Informants in this study were TKW purna, who are currently empowered through songket weaving craft programs to improve the skills and economy of TKW purna. Data collection technique using in-depth interviews, observation and documentation, were analyzed using data reduction analysis techniques, the results of this study looked at the process of empowering full migrant workers through entrepreneurship program is crafting songket weaving after empowerment was carried out. As well as looking at business development strategies and developing songket weaving crafts in the form of improving songket woven quality training, songket fabric marketing and sales, songket weaving partnership and participating in songket exihibitions